Diagnosis and epidemiologic overview of the spectrum of skin diseases in Central, Northeast Ethiopia and Southern Ethiopia - Sara Rovaris; Paola Monari; Abraham Getachew Kelbore; Takele Tadesse; Efa Ambaw Bogino; Lantesil Wondewosen; Fikirete Getachew; Mehret Techane; Shimelash Bitew; Piergiacomo Calzavara-Pinton; Aldo Morrone (Dermatology Reports)
This study analyzed data from hospitals located in three regions of Ethiopia: Addis Ababa, Northeastern Ethiopia, and Southern Ethiopia. The research aims to investigate the prevalence and contributing factors associated with skin diseases in these regions. Skin disorders represent a significant health concern in these areas, though their epidemiology differs markedly from that observed in Western countries. We collected data from 6,449 patients, considering factors like education, income, cultural habits, and access to healthcare. Patients in Southern Ethiopia generally had higher Body mass indexes and incomes and were closer to dermatology centers. The findings indicate that infectious diseases and pruritic dermatoses are the most prevalent skin conditions in all regions. The study highlights the significant impact of socio-economic status on skin health, with higher education correlating with a lower incidence of infectious diseases and sebaceous gland disorders. Overcrowding was associated with a higher occurrence of infectious diseases, emphasizing the importance of hygiene and sanitary conditions. Additionally, the distance from a patient’s residence to the hospital influenced the duration of the disease, stressing the need for better accessibility to healthcare services. In conclusion, this research offers important insights into the spectrum of skin diseases in Ethiopia, emphasizing the role of socio-economic factors and the critical need for improved healthcare access and education.